2019
DOI: 10.1108/tpm-03-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

The impact of peer evaluation on team effort, productivity, motivation and performance in global virtual teams

Abstract: Purpose This study aims to assess the effect of peer evaluations on team-level effort, productivity, motivation and overall team performance. Design/methodology/approach This study explores the impact of a peer evaluation system on 895 multicultural and transnational global virtual teams (GVTs) composed of 5,852 university students from 130 different countries. The study uses a quasi-experiment in which the group project is implemented under two conditions over two sequential iterations. In the first conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Very few studies (mixed effects: k = 3, +/−; partially negative effects: k = 2, −) found negative effects of team feedback on the dependent variables (e.g., productivity/participation, Hiltz et al, 1991; Tavoletti et al, 2019; or team performance, Hiltz et al, 1991). However, some of these studies also suggest that the negative effects of feedback depend on how it was delivered.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Very few studies (mixed effects: k = 3, +/−; partially negative effects: k = 2, −) found negative effects of team feedback on the dependent variables (e.g., productivity/participation, Hiltz et al, 1991; Tavoletti et al, 2019; or team performance, Hiltz et al, 1991). However, some of these studies also suggest that the negative effects of feedback depend on how it was delivered.…”
Section: Resultsmentioning
confidence: 99%
“…However, we also identified four studies that reported partially negative effects for subjective feedback on team mediators and team performance outcomes. Among these studies, Tavoletti et al (2019) used a quasi-experimental design and evaluated the effect of peer evaluations in an impressive sample of 895 transnational global virtual teams throughout an entire 10-week project and showed that under the subjective feedback condition, virtual teams showed lower levels of average productivity and motivation, and no clear evidence of improved team performance. The authors discuss how subjective feedback (in particular when it originates from peers) can produce counter-productive team dynamics because “group members have an incentive to intentionally distort their evaluations of peers downward as a way of enhancing their own relative performance rating” (Tavoletti et al, 2019, p. 336)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the concern arises when through knowledgeable colleagues the level of effort, productivity, motivation and performance of teams are evaluated. Then, results frequently show more significant effort, lower levels of productivity and motivation and no evidence of having exceeded the performance, which does not show the expected benefits (Tavoletti et al 2019).…”
Section: Teamworkmentioning
confidence: 94%